2022
DOI: 10.1039/d2an01105k
|View full text |Cite
|
Sign up to set email alerts
|

Development of a colloidal gold strip assay for the detection of total homocysteine in serum samples

Abstract: Homocysteine (Hcy) is an amino acid found in the human body, which has the potential to predict cardiovascular risk where timely detection and treatment are very important. In this study,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…20 Most environmental immunoassays are directed toward organic compounds; 18,19 however, this technique applied to any analyte, including metals, if a suitable antibody can be generated. [20][21][22][23] Time-resolved uoroimmunoassay (TRFIA) is a type of immunoassay that has been developed in recent decades. 24 In these assays, chelates of rare-earth lanthanide elements such as Europium and samarium are used as labels because of their intrinsic high uorescence intensity, ability to overcome highbackground interferences, and delayed relaxation time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Most environmental immunoassays are directed toward organic compounds; 18,19 however, this technique applied to any analyte, including metals, if a suitable antibody can be generated. [20][21][22][23] Time-resolved uoroimmunoassay (TRFIA) is a type of immunoassay that has been developed in recent decades. 24 In these assays, chelates of rare-earth lanthanide elements such as Europium and samarium are used as labels because of their intrinsic high uorescence intensity, ability to overcome highbackground interferences, and delayed relaxation time.…”
Section: Introductionmentioning
confidence: 99%
“…20 Most environmental immunoassays are directed toward organic compounds; 18,19 however, this technique applied to any analyte, including metals, if a suitable antibody can be generated. 20–23…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies have shown that certain diseases such as neonatal defects, arteriovenous thrombosis, diabetes, stroke, Alzheimer’s, and Parkinson’s disease are also associated with abnormal Hcy metabolism [ 9 , 11 , 12 ]. Since the high concentrations of Hcy can induce the risk of various diseases, a variety of methods for the detection of Hcy have been developed clinically to facilitate clinical diagnosis and prevention [ 13 , 14 , 15 ]. The biomarkers of DM have been studied by metabolomics, which also involve the metabolites on Hcy metabolism [ 16 ].…”
Section: Introductionmentioning
confidence: 99%